Utilization of Metakaolin and Calcite: Working Reversely in Workability Aspect—As Mineral Admixture in Self-Compacting Concrete - Fatih Özcan; Halil Kaymak (Advances in Civil Engineering)
In this work, utilization of metakaolin (MK) and calcite (C), working reversely in workability aspect, as mineral admixture in self-compacting concrete (SCC), was investigated. MK and C replaced cement in mass basis at various replacement ratios, separately and together. In total, 19 different SCCs were produced. Binder content and water to binder ratio were selected as 500 kg/m3 and 0.4, respectively. Workability tests including slump flow, T50, L-box, and V-funnel tests were performed. Consistency and setting times of binder paste were measured. While replacement of MK with cement increased the amount of plasticiser requirement, calcite worked reversely and decreased it. Reverse influence of MK and C on plasticiser requirement of SCC made possible to produce SCC at total 45% replacement ratio of MK and C together. Samples of SCC were cured in water at 20°C temperature. Compressive strengths of SCC samples were measured up to six months to evaluate the influence of MK and C, separately and together. Ultrasonic pulse velocity, abrasion, and capillary water absorption values of samples were determined at specified age. MK inclusion in concrete reduces workability, while C inclusion increases it. C and MK inclusion together remedied workability of concrete and enabled to produce SCC with high volume of admixtures. Furthermore, C incorporation increased one-day compressive strength, while MK incorporation reduced it in comparison with control concrete. In long term, C inclusion reduced compressive strength; however, MK inclusion increased it. C inclusion remedied one-day strength of concrete when it was used together with MK. MK inclusion remedied long-term compressive strength when it was used together with C and enabled to produce high-strength SCC with high volume of admixtures. SCC containing MK and C together showed better durability-related property.